Human Health and Ecological Risks Assessment of Potentially Toxic Elements in Automobile and Non-Erosive Sites in Ebonyi State, Nigeria - F S, Nworie; F I, Nwabue; N O, Omaka; SO, Ngele; C E, Oroke; AC, Ike-Amadi; N, Mgbemena; C, Onyekwere (International Journal of Chemical and Process Engineering Research, 2022)
Global concern is on the rise of ecological and human health risk associated with unregulated and unabated discharge of potentially toxic elements (PTEs) into the environment. This work investigated the concentration of PTEs, evaluated the sources and level of soil pollution and analyzed the level of ecological and human health risks. The study involves sample size (n =120) of one hundred and twenty soil samples collected from six spatial different areas of Ebonyi State. Determination of the concentration of the PTEs was executed using atomic absorption spectrophotometry. The degree of discrete distribution of the concentration of PTEs and relationship among them was achieved using descriptive statistical analysis and correlation coefficient. Automobile sites based on the result proved to have higher concentrations of PTEs in relation to nonerosive soils. The mean concentration of Zn, Cd, Pb, Ni, Fe and Cu were 689.48, 0.649, 694, 48.84, 6039.82 and 91.02 mg/kg respectively in automobile sites while in nonerosive soils, it was 8.33, 0.26, 2.82, 1.21, 11.99 and 4.36 mg/kg respectively. The overall ecological risk index and degree of contamination are 317.21 and 59.69 for automobile sites and 72.22 and 2.76 for non –erosive sites respectively. This indicates automobile sites to be of high degree of contamination and of high ecological risk. Evaluation of carcinogenic risk shows that Zn, Cu, Ni and Pb are of high cancer risks in the automobile sites for children and adults. Among all the studied PTEs, Zn and Pb poses significant health and ecological risks.